Pengaruh Kompetensi dan Kepuasan Kerja Terhadap Kinerja Pegawai di Badan Meteorologi Klimatologi dan Geofisika Pusat Kemayoran Jakarta - Nadhifa Rima Rasya; Dadan Ahmad Fadili (Peneliti.net, 2022)
This research was conducted with the aim of knowing, explaining, and analyzing the effect of competence and job satisfaction on employee performance at the Meteorology, Climatology, and Geophysics Agency of Kemayoran Jakarta Center using quantitative methods, namely descriptive and verification analysis. In this study, we used scale-range analysis techniques and path analysis with the help of Microsoft Excel and SPSS software as tools to process data. The sample in this study amounted to 299 respondents using a simple random sampling technique. The results of the verification research, namely the correlation of competence with job satisfaction of 0.750, have a strong, positive, and significant correlation. The partial effect of competence on employee performance is 34.9%; the partial effect of job satisfaction on employee performance is 31.5%. The simultaneous influence of competence and job satisfaction on employee performance is 66.4%, and the remaining 33.6% is the influence of other variables not examined.